Dicrostonyx nelsoni Merriam 1900 ... - Don E. Wilson; Russell A. Mittermeier; Thomas E. Lacher, Jr (Lynx Edicions, 2017)
36. Nelson's Collared Lemming Dicrostonyx nelsoni French: Lemming de Nelson / German: Nelson-Halsbandlemming / Spanish: Lemming de collar de Nelson Other common names: St. Lawrence Island Collared Lemming Taxonomy. Dicrostonyx nelsoni Merriam, 1900, “St. Michaels [Norton Sound], Alaska.” Dicrostonyx nelsoni is monotypic and is not recognized as a distinct species by some, but instead considered a subspecies of D. groenlandicus. Other taxonomists, based on chromosomal differences and breeding studies, suggest that there are up to three species of collared lemming in Alaska alone. Distribution. W Alaska, from Seward Peninsula S to Alaska Peninsula and Unimak I (previously considered D. peninsulae), and including population on St. Lawrence I (previously considered D. exsul). Descriptive notes. Head—body 126-135 mm,tail 9-13 mm; weight 45-72 g. Nelson's Collared Lemming is stocky, with relatively short limbs and tail. It is seasonally dimorphic, white in winter and grayish brown in summer. There is usually a ... : Published as part of Don E. Wilson, Russell A. Mittermeier & Thomas E. Lacher, Jr, 2017, Cricetidae, pp. 204-535 in Handbook of the Mammals of the World – Volume 7 Rodents II, Barcelona :Lynx Edicions on page 298, DOI: 10.5281/zenodo.6707142 ...